Investigating the Mechanism of Inhibition of Cyclin-Dependent Kinase 6 Inhibitory Potential by Selonsertib: Newer Insights Into Drug Repurposing - Baig, Mohammad Hassan; Yousuf, Mohd.; Khan, Mohd. Imran; Khan, Imran; Ahmad, Irfan; Alshahrani, Mohammad Y.; Hassan, Md. Imtaiyaz; Dong, Jae-June (Frontiers in Oncology, 2022)
Cyclin-dependent kinases (CDKs) play significant roles in numerous physiological processes and are being considered an attractive drug target for cancer, neurodegenerative and in-flammatory diseases. In the present study, we have aimed to investigate the binding affinity and inhibitory potential of selonsertib towards CDK6. Using the drug repurposing approach, we performed molecular docking of selonsertib with CDK6 and observed a significant binding affinity. To ascertain, we further performed essential dynamics analysis and free energy calculation, which suggested the formation of a stable selonsertib-CDK6 complex. The in-silico findings were further experimentally validated. The recombinant CDK6 was ex-pressed, purified and treated with selonsertib. The binding affinity of selonsertib to CDK6 was estimated by fluorescence binding studies and enzyme inhibition assay. The results in-dicated an appreciable binding of selonsertib against CDK6, which subsequently inhibits its activity with a commendable IC50 value (9.8 μM). We concluded that targeting CDK6 by selonsertib can be an efficient therapeutic approach towards cancer and other CDK6-related diseases. These observations provide a promising opportunity to utilize selonsertib to address CDK6-related human pathologies.